Evaluation of Personnel Information System Performance at the Department of Population and Civil Registration of Bengkayang Regency Using COBIT 5 - Tania Linda; Agustinus Fritz Wijaya (Universitas Bina Darma, 2021)
The Bengkayang Regency Population and Civil Registry Service is an institution that aims to record population administration data which includes data including birth data, marriage data and death data, identity cards, family cards, and children's identity cards. The Dukcapil Service Office is one of the services that serves the community, especially in population management. This study aims to refer to the version 5 COBIT framework for reviewing the management of Personnel SI at the Bengkayang Regency Population and Civil Registry Service. The domain used in COBIT 5 is